Proton exchange membranes from sulfonated poly(ether ether ketone) reinforced with silica nanoparticles. (November 2013) - Unnikrishnan, Lakshmi; Mohanty, Smita; Nayak, S. K.
The feasibility of sulfonated poly(ether ether ketone) (SPEEK) membranes reinforced with unmodified silica (SiO2 ) and modified silica (SiO2 –SO3 H) nanoparticles as proton exchange membranes (PEMs) was investigated here. The sulfonated membranes were characterized for degree of sulfonation, thermal stability, as well as water/methanol uptake properties. The incorporation of SiO2 increased the hydrophilic behavior thus allowing more water retention, which facilitated an easy pathway for proton transfer. However, a reduction in proton conductivity was observed. The strong –SO3 H/–SO3 H interaction between SPEEK chains and SiO2 –SO3 H led to ionic cross-linking in the membrane structure, which compensated for this decrement in proton conductivity. The fuel cell performance study revealed the potential of SPEEK/SiO2 –SO3 H nanocomposite membrane to act as an efficient PEM for fuel cell application.